Sociodemographic and behavioral aspects in the consumption of organic foods - Ribeiro, Letícia; Silveira, Catia da Silva; Helbig, Elizabete (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The objective of this research was to characterize consumers and non-consumers of organic food in terms of sociodemographic and behavioral aspects, identifying the variables that most affect consumption. This is a qualitative, cross-sectional descriptive study, with a non-probabilistic convenience sample. For this purpose, an online questionnaire was used, which was applied to people aged 18 years or over, consumers of organic or non-organic foods, living in Brazil, who had access to e-mail or social networks; carried out from February to April 2021. The data collected were analyzed using descriptive and association statistical techniques. A total of 3,342 people participated in the survey, 2,546 (76%) consumers of organic food and 796 (24%) non-consumers. Being a consumer or not of organic food showed a significant relationship with the variables age group, marital status, number of children, family income, responsible for purchases and in relation to knowing its concept. The biggest motivations for consumption were the affordable price and health, with the highest indication as a limitation, the high price. Both consumers and non-consumers of organic foods are unaware of its concept, with price being the most relevant aspect for its acquisition. Knowledge of these aspects can contribute to the improvement of public policies aimed at this market niche.